EVALUATION OF THE MICROBIAL PROFILE AND ANTIBIOTIC RESISTANCE OF BACTERIA CAUSING URINARY TRACT INFECTION IN THE CHILDREN OF KYIV REGION - О. Lavrenchuk; І. Bagdasarova (Ukrainian Journal of Nephrology and Dialysis, 2016)
The rapid growth of the acquired resistance of bacteria to antibacterial agents requires a revision of the selection ofempirical antimicrobial therapy in children with urinary tract infection (UTI).The aim of this work was to investigate the etiological structure of uropathogen flora and its sensitivity to nitrofurantoin and antibacterial drugs ofother classes in children with UTI in Kyiv and region.Materials and methods. Were examined in 95 children aged 3 to 17years in the aediatric Nephrology Department of, Institute of Nephrology NAMS of Ukraine” on the basis of clinical hospital №7 Kyiv city in 2015-2016. The disease duration ofthepatients rangedfrom 3 months to 4years.Results.The microbial spectrum of the urine depended on theform of pyelonephritis, but all patients were dominated by enterobacteria E. coli and Kl. pneumoniae. The greatest number of patients was resistant to ampicillin, co-trimoxazol and cefuroxime – 10.5% of patients with acute and 17.2% with chronic pyelonephritis. The highest sensitivity was preserved in all patients before medications meronem and gentamicin – 100% and 94.7%, respectively. Most children in Kyiv and Kyiv region showed a high sensitivity to nitrofurantoin:furamag – 78.9-75.8%,furagin - 63.8-65.5%. Comparative analysis of therapeutic efficiency of drugsfuramag and co-trimoxazol, demonstrated greater therapeutic efficacy of nitro- furans in the absence of recurrences, compared with co-trimoxazol (Oto 1.68withp=0.021).Conclusions. Among the causative agents of UTI in children of the city of Kyiv and Kyiv region was dominated by gram-negativeflora - E. coli and Kl. pneumoniae. High sensitivity to nitrofurantoin drugs, especiallyfuramag, cephalosporins, and gentamicin and meronem was documented. High rates of resistance to penicillin and co-trimoxazol was revealed. The use of the drugfuramag contributed to a more rapid, complete andpersistent normalization ofclinical and laboratory parameters in children with UTI.